1994
DOI: 10.1037/0022-3514.66.5.934
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in dispositional expressiveness: Development and validation of the Emotional Expressivity Scale.

Abstract: Although emotional expressivity figures prominently in several theories of psychological and physical functioning, limitations of currently available measurement techniques impede precise and economical testing of these theories. The 17-item Emotional Expressivity Scale (EES) was designed as a self-report measure of the extent to which people outwardly display their emotions. Reliability studies showed the EES to be an internally consistent and stable individual-difference measure. Validational studies establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
363
1
22

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(409 citation statements)
references
References 66 publications
23
363
1
22
Order By: Relevance
“…Posteriormente se procedió a describir las variables en estudio (apego y DRE) y a identificar diferencias por género en las DRE mediante una prueba t para muestras independientes, a la luz de antecedentes que documentan que las mujeres expresarían más sus emociones que los hombres (e.g., Kring, Smith & Neale, 1994;Mendes, Reis, Seery & Blascovich, 2003) y experimentarían sus emociones con mayor claridad (Barrett, Lane, Sechrest & Schwartz, 2000). Para el contraste de las hipótesis se realizó un análisis multivariado de la varianza (MANOVA), dado que es una prueba de mayor potencia cuando se busca evaluar el efecto sobre un conjunto de variables dependientes correlacionadas entre sí, controlando la tasa de error tipo II (Hair et al, 1987(Hair et al, /1999.…”
Section: Análisis De Datosunclassified
“…Posteriormente se procedió a describir las variables en estudio (apego y DRE) y a identificar diferencias por género en las DRE mediante una prueba t para muestras independientes, a la luz de antecedentes que documentan que las mujeres expresarían más sus emociones que los hombres (e.g., Kring, Smith & Neale, 1994;Mendes, Reis, Seery & Blascovich, 2003) y experimentarían sus emociones con mayor claridad (Barrett, Lane, Sechrest & Schwartz, 2000). Para el contraste de las hipótesis se realizó un análisis multivariado de la varianza (MANOVA), dado que es una prueba de mayor potencia cuando se busca evaluar el efecto sobre un conjunto de variables dependientes correlacionadas entre sí, controlando la tasa de error tipo II (Hair et al, 1987(Hair et al, /1999.…”
Section: Análisis De Datosunclassified
“…Participants viewed six brief emotional film clips (ranging in length from 264 to 350 s) that represented three emotion domains: happy, sad, and fear (two clips from each domain). 2 These film clips have been successful in eliciting both experienced and expressed emotion in previous research (Fredrickson & Levenson, 1996;Kring, Kerr, Smith, & Neale, 1993;Kring et al, 1994), and they have been shown to elicit higher ratings of their intended emotion than other similar clips (Kring, Rauhuff, & Gordon, 1992). The film clips included scenes of slapstick comedy, children with a dying parent, a man being swarmed with cockroaches, and a man nearly falling off the ledge of a tall building.…”
Section: Stimulimentioning
confidence: 99%
“…vanderbilt.edu. 1977; Lang, 1995;Levenson, 1994;Leventhal, 1984;Plutchik, 1993). In our view, emotional expressivity reflects the extent to which individuals outwardly display their emotions (Kring, Smith, & Neale, 1994), which is similar to Gross and John's (1997) conceptualization; "the behavioral changes (e.g., facial, postural) that typically accompany emotion" (p. 435); it is also similar to Halberstadt and colleagues' definition: "a persistent pattern or style in exhibiting nonverbal and verbal expressions that often but not always appear to be emotion related'' (Halberstadt, Cassidy, Stifter, Parke, & Fox, 1995, p. 93). The degree to which the expressive, experiential, and physiological emotion components correspond to one another varies depending on a number of social, cultural, and situational factors (e.g., Adelrnann & Zajonc, 1989;Ekman, Friesen, & Ellsworth, 1982;Lang, 1968;Lang, Bradley, & Cuthbert, 1990;Miller & Kozak, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This account may pose problem because it relies on the assumption that emotional components have specific meaning, that is, correspond to particular classes of emotion, a question still debated in the psychological literature (Scherer and Ellgring 2007a). Moreover, it assumes that some situations invariably lead to particular emotional experiences, while it is reasonable to expect individual differences in the way people react to a given situation (Davidson 1992;Kring et al 1994). According to that model, the evaluation of a signaller's intentions based on the relationship between symbolic and emotional signals should therefore take into account a person's prototypical responsiveness (Ekman 1985).…”
Section: Encoding Decoding and Intentionality In Communicationmentioning
confidence: 99%